A Frontal Retrobulbar Mucocele with Lytic Lesion at Orbital Plate and Orbital Ridge, Rare Case Report (Bangladesh Journal of Neuroscience, 2014)
Mucoceles can occurs when there is obstruction of drainage passage of mucosa of paranasal sinus. Some time it can cause pressure at eye ball and can cause proptosis. A old man admitted at Bangabandhu Sheikh Mujib Medical University with the complaints of right orbital swelling with proptosis of right eye ball. Also complaints of progressive visual bluring & headache for some time. The mucocele was operated by frontal craniotomy and excised completely. As this is a ran case and so few an reported. Bangladesh Journal of Neuroscience 2011; Vol. 27 (2) : 105-107 DOI: http://dx.doi.org/10.3329/bjn.v27i2.17578